Implementation Of PIECES Framework In Evaluating Academic Information Systems - RIZKI DWI IRIANTI; Novi Prastiti; Meidya Koeshardianto; Azzizul Yulia (Jurnal Simantec, 2026)
The evaluation of an information system is crucial for identifying its strengths and weaknesses, allowing for the development of a better system. The Academic Information System (SIAKAD) of University of Trunojoyo Madura, Madura, used by various user groups, has the potential to generate different levels of user satisfaction. This study aims to evaluate SIAKAD using the PIECES framework, which includes indicators such as Performance, Information and Data, Economy, Control and Security, Efficiency, and Service. Data for the research were collected through a questionnaire distributed to active SIAKAD users. The evaluation results revealed several shortcomings in SIAKAD, specifically in the areas of Performance (31.23%), Information and Data (25.9%), Control and Security (29.6%), and Efficiency (32.5%). However, SIAKAD performed well in the Economy (68.1%) and Service (50.7%) indicators. These findings suggest that SIAKAD needs improvement in aspects like system speed, information quality, access control, and user efficiency. Conversely, the system shows strengths in cost-effectiveness and user service.